2006
DOI: 10.1158/0008-5472.can-06-2206
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aromatase Activity of Phytochemicals in White Button Mushrooms (Agaricus bisporus)

Abstract: White button mushrooms (Agaricus bisporous) are a potential breast cancer chemopreventive agent, as they suppress aromatase activity and estrogen biosynthesis. Therefore, we evaluated the activity of mushroom extracts in the estrogen receptor-positive/aromatase-positive MCF-7aro cell line in vitro and in vivo. Mushroom extract decreased testosterone-induced cell proliferation in MCF-7aro cells but had no effect on MCF-10A, a nontumorigenic cell line. Most potent mushroom chemicals are soluble in ethyl acetate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
95
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 51 publications
3
95
0
1
Order By: Relevance
“…A. bisporus contains antioxidants (26), conjugated linoleic acid (5) and high amounts of vitamins D and B (14). A very recent study found that women consumed fresh mushrooms daily, were 64% less likely to develop breast cancer and risk was reduced by 90% (32).…”
Section: Introductionmentioning
confidence: 99%
“…A. bisporus contains antioxidants (26), conjugated linoleic acid (5) and high amounts of vitamins D and B (14). A very recent study found that women consumed fresh mushrooms daily, were 64% less likely to develop breast cancer and risk was reduced by 90% (32).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen responsible for the development of breast cancer. The women who consumed more than 10g of fresh A. bisporus daily, were 64% less likely to develop breast cancer, while those that combined a mushroom diet with regular green tea, reduced the risk of breast cancer by nearly 90% (Chen et al 2006;Hong et al 2008). A. bisporus contains small amounts of the carcinogenic mycotoxin agaritine, which is a health hazard.…”
Section: Introductionmentioning
confidence: 99%
“…3 Mushrooms and mushroom extracts have been shown to possess anticarcinogenic properties, antimutagenic activity and to stimulate immune responsiveness in experimental models, both in vitro and in vivo. [4][5][6][7][8][9][10] Laboratory studies have demonstrated that mushrooms inhibited aromatase activity in breast cancer cell line and suppressed growth and invasiveness of metastatic breast cancers. 9,10 Despite the demonstration of the anticarcinogenic effect of mushrooms by many experimental studies, little relevant epidemiologic evidence is available from human populations.…”
mentioning
confidence: 99%